A national research agenda for pre-hospital emergency medical services in the Netherlands: a Delphi-study. Issue 1 (December 2016) - van de Glind, Irene; Berben, Sivera; Zeegers, Fon; Poppen, Henk; Hoogeveen, Margreet; Bolt, Ina; van Grunsven, Pierre; Vloet, Lilian
Abstract Background In pre-hospital Emergency Medical Services (EMS) more research is needed to direct and underpin care delivery and inform policy. To target future research efforts, this study aimed to determine future research priorities with representatives of the EMS field. Methods A four-round online Delphi survey was used to discuss different viewpoints and reach consensus on research priorities. A multidisciplinary panel of experts was recruited in the field of pre-hospital EMS and adjoining (scientific) professional organisations (n  = 62). 48 research topics were presented in Delphi I, and the panel was asked to rate their importance on a 5-point scale. In Delphi II and III the panel selected their priority research topics, and arguments why and suggestions for research questions were collected and reported back. In Delphi IV appropriateness of the remaining topics and agreement within the expert panel was taken into account to make up the final list of research priorities. Results The response on the Delphi-survey was high: 95 % (n  = 59; Delphi I); 97 % (n  = 60, Delphi II); 94 % (n  = 58, Delphi III); 97 % (n  = 60, Delphi IV). The panel reduced the number of research topics from 48 topics in Delphi I to 12 topics in Delphi III. A variety of arguments and suggestions for research questions were collected, giving insight in reasons why research on these topics in the near future is needed. Delphi IV showed an adequate level of agreement with respect to the 12 presented research topics. The following 9 topics were rated as appropriate for the national pre-hospital EMS research agenda: Non-conveyance to the hospital (ranked highest); Performance measures for quality of care; Hand over/registration/exchange of patient data; Care and task substitution; Triage; Assessment of acute neurologic signs & symptoms; Protocols and protocol adherence; Immobilisation; and Open/secure airway. Discussions The research priorities identified in our study resemble those in other studies. However, the topic 'non-conveyance to the hospital' was determined as a priority in this study but not in other studies. Conclusions The national pre-hospital EMS research agenda can focus future research efforts to improve the evidence base and clinical practice of pre-hospital emergency medical services. Dissemination and implementation of the research agenda deserves careful attention.